The effectiveness of collaboration among special and general education teachers in the Kingdom of Saudi Arabia - Alhossyan, Fawaz (Edelweiss Applied Science and Technology, 2025)
This study examined the attitudes of special and general education teachers toward collaboration in an inclusive classroom setting. A semi-structured interview design was used to gain in-depth insights and explore the effectiveness of collaboration between special education and general education teachers in the Kingdom of Saudi Arabia. After an initial screening questionnaire, six educators—four special education teachers and two general education teachers—were chosen for individual telephone interviews. The data revealed four core themes: (1) professional development, (2) limited communication between teachers, (3) insufficient resources, and (4) time constraints. Further investigation of collaborative practices between special and general education teachers is recommended to enhance inclusion.